ANALISIS KETAHANAN 10 GENOTIPE KACANG HIJAU (Vigna radiata L.) ASAL PROVINSI RIAU TERHADAP CEKAMAN SALINITAS - Imra Atul Uswah; Herman Herman; Dewi Indriyani Roslim (DINAMIKA PERTANIAN, 2018)
Mung bean (Vigna radiata L.) is one of the important because it has a high nutritional value, so many Indonesia consumption its crop. The production of mung beans is still relatively low due to the reduced availability of land, so it is necessary to use marginal land such as saline land. Therefore, this study aims to analyze the resistance of 10 mung bean genotypes (Vignaradiata L.) from Riau Province on salinity stress. Mung beans seeds of 10 genotypes were grown in polybags with treatments including Control and Treatment saline 7 g/L NaCl of Dolphin salt with 7 replications for 66 HST. The interval of watering saline treatment was five days on time the plant begins to bloom. All genotypes showed different morphological responses to salinity stress. Characteristic of 10 genotypes of mung beans from Riau Province based on salinity stress treatment was obtained a significantly different result on the character of productive branch number, plant height, flowering period, number of pods, pod length, seed number, 100 seed weight, and root length. The tolerant genotype of the salinity of Rohul origin 1 (RU1) was superior to plant height, flowering period, number of pods, number of seeds, and root volume. Genotypes from Pelalawan (P) for branch character, Inhu (IU) genotype was for long pods and 100 seeds, and Rohul 2 (RU2) genotype was for long root characters.